2005
DOI: 10.1111/j.1747-6593.2005.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use and Groundwater Use in Hebei Plain, China

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Low mineralized water with a salt content of 1.0 g/cm 3 was used throughout the experiment. (Xu et al 2005a). Salinity sensors and tensiometers were installed at different depths (5, 20, 45, 70, 100 cm and then at an interval of 30 cm) through observation holes on the sides of the columns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low mineralized water with a salt content of 1.0 g/cm 3 was used throughout the experiment. (Xu et al 2005a). Salinity sensors and tensiometers were installed at different depths (5, 20, 45, 70, 100 cm and then at an interval of 30 cm) through observation holes on the sides of the columns.…”
Section: Methodsmentioning
confidence: 99%
“…After evaluating several commonly recognized numerical methods (the high-order difference for derivative in time, the second-order upwind implicit scheme and the characteristic finite element method), it is concluded that the Galerkin-type finite element method is capable of overcoming the calculation difficulties. A detailed description of SWSTM's numerical solution can be found in Xu et al (2005a).…”
Section: Numerical Solutionmentioning
confidence: 99%
“…The large water infrastructure exemplified by the south to north water diversion project (SNWDP) in BTH does contribute to groundwater recharge (Aeschbach‐Hertig & Gleeson, 2012; Kattel et al, 2019), reduces drawdown rate of the water table, improves GDEs and subsequently elevate water efficiency (Ye, Duan, Chu, Xu, & Mao, 2014). The selection of water‐saving irrigation technology and crop varieties is advised for soil conservation and sustainable use of groundwater in the region (Xu et al, 2005; Zou et al, 2011). Water conservation approaches such as the adoption of sprinkler irrigation, regulation of pumping restrictions (including restrictions on the diameter and depth of wells), construction of industrial waterworks, and regulation of water tax policies are important for groundwater recharging and water saving programs (Endo, 2015).…”
Section: Synthesis Of Framework and Recommendationsmentioning
confidence: 99%
“…There are cases of increased groundwater contamination with nitrogen and heavy metals due to regional land use intensifications and related public health concern (Chen et al, 2007; Han, Currell, Cao, & Hall, 2017; Liu & Ma, 2020). Further, groundwater hydrology is influenced by seawater intrusion, riverbank habitat destructions across the coastal zones, which have triggered water shortage and environmental degradation with negative impact on socioeconomic development (Xu et al, 2005).…”
Section: Key Challenges Of Water Resource Management In Beijing‐tianj...mentioning
confidence: 99%
“…Over the years, the water-intensive economic development in northern China is hindered by severe water shortages [4,5]. The northern region, where more than 150 million people live, has faced a dramatic reduction as high as 150 billion m 3 of groundwater reserves over recent decade, causing a significant decrease in the water supply across Beijing, Tianjin and Hebei [6,7]. Groundwater reserves have played a vital role in protecting the environments against droughts over millennia [8].…”
Section: Introductionmentioning
confidence: 99%